The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1741-3737.2008.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Contextual Influences on Parenting in Mexican American Families

Abstract: Family stress theory can explain associations between contextual stressors and parenting. However, the theory has not been tested among Mexican Americans or expanded to include cultural-contextual risks. This study examined associations between neighborhood, economic, and acculturative stressors and parenting behaviors in a sample of 570 two-parent Mexican American families. Results support the negative impact of economic stress on parenting through parental depressive symptoms. Neighborhood stress influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
149
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 73 publications
14
149
2
Order By: Relevance
“…Together, these results provide support for the extant literature linking NSCSP to developmental outcomes (Caughy et al, 2012;Kohen et al, 2008;McNulty & Bellair, 2003;Tolan et al, 2003) In relation to the effects of NSCSP on parenting, higher levels of neighborhood resources, social cohesion, and perception of neighborhood safety were associated with lower levels of parenting stress and better parental well-being, whereas poorer neighborhood quality was linked with higher levels of parenting stress and poorer parental well-being. These results are consistent with evidence from other researchers showing that the structural characteristics and social processes of neighborhoods can have an effect on parental functioning and well-being (Chung & Steinberg, 2006;Kohen et al, 2008;Kotchick et al, 2005;Law & Barber, 2007;White et al, 2009). Higher levels of parenting stress and poorer parental well-being were associated with poorer parent-child relations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Together, these results provide support for the extant literature linking NSCSP to developmental outcomes (Caughy et al, 2012;Kohen et al, 2008;McNulty & Bellair, 2003;Tolan et al, 2003) In relation to the effects of NSCSP on parenting, higher levels of neighborhood resources, social cohesion, and perception of neighborhood safety were associated with lower levels of parenting stress and better parental well-being, whereas poorer neighborhood quality was linked with higher levels of parenting stress and poorer parental well-being. These results are consistent with evidence from other researchers showing that the structural characteristics and social processes of neighborhoods can have an effect on parental functioning and well-being (Chung & Steinberg, 2006;Kohen et al, 2008;Kotchick et al, 2005;Law & Barber, 2007;White et al, 2009). Higher levels of parenting stress and poorer parental well-being were associated with poorer parent-child relations.…”
Section: Discussionsupporting
confidence: 92%
“…Developmental research on neighborhood effects on child and youth development have found a mediational path via parental psychological distress, family processes, and parent-child relationship constructs (Kohen et al, 2008;Kotchick, Dorsey, & Heller, 2005;Law & Barber, 2007;White, Roosa, Weaver, & Nair, 2009). Kohen et al (2008) reported that lower neighborhood cohesion was associated with maternal distress and family dysfunction, which, in turn, were correlated to poor quality parenting behaviors, and ultimately, poorer child outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally informed ecological perspectives for understanding marriage further emphasize the importance of disentangling the sources of contextual stress couples of Mexican origin may encounter when examining potential associations with spouses' psychological distress and subsequent marital functioning (Helms, Supple, & Proulx, 2011;White et al, 2009). This literature emphasizes that economic pressure should be treated as conceptually distinct from stress related to the process of cultural adaptation, which is defined as the challenges associated with negotiating two sets of cultural norms and values (Knight et al, 2009;Phinney, 1990).…”
Section: Theoretical and Empirical Foundationsmentioning
confidence: 97%
“…These differences can lead to less-than-optimal family functioning (Smokowski et al, 2008) and family (cultural) stress (Martinez, 2006). Economic stress has been found to be positively related to acculturation stress (Stein, Gonzalez, & Huq, 2012;White et al, 2009). This association may be due to several mechanisms, such as a larger discrepancy between parental and child acculturafion in lower SES ethnic minority families.…”
mentioning
confidence: 96%